Age Is Just a Number: Patient Age Does Not Affect Outcome Following Surgery for Osteoporotic Vertebral Compression Fractures. Issue 7 (September 2021) - Gupta, Anmol; Cha, Thomas; Schwab, Joseph; Fogel, Harold; Tobert, Daniel; Qureshi, Sheeraz; Hecht, Andrew; Bono, Christopher M.; Hershman, Stuart
Study Design: Retrospective study. Objective: Multiple studies have shown that osteoporotic patients are at an increased risk for medical and surgical complications, making optimal management of these patients challenging. The purpose of this study was to determine the relationship between patient age and the likelihood of surgical complications, mortality, and 30-day readmission rates following surgery for osteoporotic vertebral compression fractures (OVCFs). Methods: A retrospective analysis of the American College of Surgeons National Surgery Quality Improvement Project (ACS-NSQIP) database from 2007 to 2014 identified 1979 patients who met inclusion criteria. A multivariate logistic regression analysis was conducted to calculate odds ratios (OR), with corresponding P values and 95% confidence intervals, of the relationship between age (treated as a continuous variable) and perioperative mortality, surgical complications, and 30-day readmission rates. Results: Younger patients were statistically more likely to endure a minor (OR = 0.98; P = .002) or major complication (OR = 0.97; P = .009). The older a patient was, on the other hand, the higher the likelihood that patient would be readmitted within 30 days of surgery (OR =1.02; P = .004). Mortality within the 30-day perioperative period was not statistically correlated with age. Conclusions: The impact of age on adverse outcomes following surgery for OVCF is mixed. While younger patients are more likely to endure complications, older patients are more likely to be readmitted within 30 days following surgery. Patient age showed no correlation with mortality rates. In the setting of surgical treatment for an OVCF, a patient's age can help determine the risk of complications and the rate of readmission following intervention.